The Effect of Adding Butterfly Pea Flower Powder (Clitoria rernatea L.) in Feed on The Color Brightness of Guppy Fish (Poecilia reticulata) - Afriani, Sari; Auja, Nailul; Gunawan, Gunawan (Jurnal Perikanan Terpadu, 2024)
The Guppy fish (Poecilia reticulata) is a popular freshwater ornamental fish in Indonesia, presenting good opportunities for cultivation. However, one common issue faced by fish farmers is the low brightness of the fish's colors, which lowers its market value and affects consumer demand. One approach to address this is by adding pigmentation ingredients to the feed to enhance the fish's body color. The aim of this study was to determine the effect of adding butterfly pea flower powder (Clitoria ternatea L.) to the feed on the color brightness of Guppy fish (Poecilia reticulata). The research used an experimental method with a Completely Randomized Design (CRD) and a non-factorial layout, consisting of five treatments and three repetitions. The study was conducted over 10 days, with the following treatments: P0 (control, without butterfly pea flower powder), P1 (feed with 3% butterfly pea flower powder), P2 (feed with 6% butterfly pea flower powder), P3 (feed with 9% butterfly pea flower powder), and P4 (feed with 12% butterfly pea flower powder). The ANOVA test showed that adding butterfly pea flower powder in various concentrations significantly affected (P<0.05) the increase in color brightness of guppy fish. Duncan's Multiple Range Test (DMRT) indicated that P4 resulted in the highest increase in color brightness, with a value of 2.46, significantly different from P0 (control), but not significantly different from P2 and P3 treatments